Black twig borer, Xylosandrus compactus (Eichhoff), as a potential threat to the coffee production - Túler, Amanda C.; Valbon, Wilson R.; Rodrigues, Hígor S.; Noia, Luína R.; Santos, Lucas M. L.; Fogaça, Isac; Rondelli, Vando M.; Verdin-Filho, Abraão C. (Revista de Ciencias Agrícolas, 2019)
In robusta coffee, Coffea canephora, the black twig borer Xylosandrus compactus (Eichhoff) (Coleoptera: Curculionidae) causes considerable damage. Although this has been reported in many crops for years in Brazil, recently, the injury caused by X. compactus in coffee has been ignored. This present study aimed to report the current status of X. compactus in Brazil, and to investigate its attack frequency in different robusta coffee genotypes. In this study, we reported the occurrence of X. compactus in robusta coffee plants in the state of Rondônia for the first time. We also evaluated the occurrence of this pest in different robusta coffee genotypes in the state of Espírito Santo. In all plants, the plagiotropic branches were attacked; however, the genotypes G2, G6, G8, G20, G48, G50, G51 and G52 showed a high number of attacked plagiotropic branches, whereas the genotypes G24 and G41 showed a low attack frequency. Thus, these can be promising candidates for pest resistance studies. Moreover, it was reported that Almeidea rubra, Alseis floribunda, Plinia grandifolia and Casearia Sylvestris can serve as hosts of X. compactus. Thus, our findings suggest that X. compactus is a threat to coffee production, and that future studies are necessary to find appropriate tools for its management.